2012
DOI: 10.1073/pnas.1203280109
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine deiminase 2-catalyzed histone H3 arginine 26 citrullination facilitates estrogen receptor α target gene activation

Abstract: Cofactors for estrogen receptor α (ERα) can modulate gene activity by posttranslationally modifying histone tails at target promoters. Here, we found that stimulation of ERα-positive cells with 17β-estradiol (E2) promotes global citrullination of histone H3 arginine 26 (H3R26) on chromatin. Additionally, we found that the H3 citrulline 26 (H3Cit26) modification colocalizes with ERα at decondensed chromatin loci surrounding the estrogen-response elements of target promoters. Surprisingly, we also found that cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
202
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 175 publications
(209 citation statements)
references
References 36 publications
6
202
0
1
Order By: Relevance
“…In addition, we found strong nuclear anti-pan-citrulline staining in these lesions (Fig. 2D, inset bottom image), which is in line with our previous studies showing that PAD2-mediated histone deimination regulates gene expression (9,10,14,21). Because the anti-human PAD2 antibody likely cross-reacts with endogenous mouse PAD2, we also stained these tissues with an anti-FLAG antibody to specifically stain the PAD2 fusion protein.…”
Section: Recombinant Pad2 Is Expressed In the Skin And Tumor Tissue Osupporting
confidence: 67%
See 1 more Smart Citation
“…In addition, we found strong nuclear anti-pan-citrulline staining in these lesions (Fig. 2D, inset bottom image), which is in line with our previous studies showing that PAD2-mediated histone deimination regulates gene expression (9,10,14,21). Because the anti-human PAD2 antibody likely cross-reacts with endogenous mouse PAD2, we also stained these tissues with an anti-FLAG antibody to specifically stain the PAD2 fusion protein.…”
Section: Recombinant Pad2 Is Expressed In the Skin And Tumor Tissue Osupporting
confidence: 67%
“…To generate the MMTV-FLAG-PAD2 construct, human PAD2 cDNA was subcloned from pcDNA3.1-FLAG-PAD2 (14) into the EcoRI sites of the MMTV-SV40-Bssk plasmid (Addgene plasmid #1824), originally generated in the laboratory of Dr. Philip Leder at Harvard Medical School (Boston, MA; ref. 15).…”
Section: Generation Of Mmtv-flag-pad2 Micementioning
confidence: 99%
“…First, methyl groups may be removed directly from arginine by demethylation, similar to mechanisms used by JmjC proteins to demethylate methyl lysine (27). Second, methylated arginine may be converted to citrulline, similar to the products of peptidylarginine deiminase (PADI) enzymes (27)(28)(29)(30). Third, methyl arginine may be removed by more extensive cleavage of histone tails by proteolysis, thus using a clipping process (3).…”
Section: Significancementioning
confidence: 99%
“…For example, PADI4 catalyzed deimination of histone H3 at Arg17 and histone H4 at Arg 3 has been linked to transcriptional repression (Cuthbert et al 2004;Wang et al 2004). Conversely, citrullination of histone H3R26 by PADI2 has been shown to facilitate transcriptional activation at target genes (Zhang et al 2012). More recently, Christophorou et al (2014) have demonstrated that citrullination of histone H1 leads to chromatin decondensation during pluripotency.…”
Section: Introductionmentioning
confidence: 99%